2012
DOI: 10.5194/astra-8-29-2012
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on ultra-high-energy neutrino flux from radio observations of the Moon

Abstract: Abstract. The NuMoon project aims to study ultra-highenergy neutrinos and cosmic rays by using radio telescopes to search for short pulses from the Moon. These pulses are created when a neutrino or cosmic ray impinges on the Moon and interacts below the lunar surface. Part of the energy is converted into a hadronic shower, which emits radio emission in a process known as the Askaryan effect. In the first phase of the NuMoon project, 46 hrs of data were collected with the Westerbork Synthesis Radio Telescope in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The technical requirements on radio telescopes are access to full time-domain voltages of the receiver and multiple beams on-and off-Moon, making not all telescopes suitable for these studies. Past observations have been performed most notably by the Parkes [633] and Westerbork telescopes [634] and the EVLA [635], with past and on-going work being performed with LOFAR [636,637]. The next step in sensitivity will be obtainable with the Square-Kilometre Array (SKA) [632,[638][639][640].…”
Section: Uhe Neutrino Detection In Lunar Regolithmentioning
confidence: 99%
“…The technical requirements on radio telescopes are access to full time-domain voltages of the receiver and multiple beams on-and off-Moon, making not all telescopes suitable for these studies. Past observations have been performed most notably by the Parkes [633] and Westerbork telescopes [634] and the EVLA [635], with past and on-going work being performed with LOFAR [636,637]. The next step in sensitivity will be obtainable with the Square-Kilometre Array (SKA) [632,[638][639][640].…”
Section: Uhe Neutrino Detection In Lunar Regolithmentioning
confidence: 99%
“…All current [1,2] and future [3,4,5] experiments aiming to use the upper lunar surface layers as a medium for ultra-high-energy (UHE) particle detection via the Askaryan effect involve observing the Moon from large distances, either via satellite, or from the Earth itself. While Askaryan pulses are characterised by their broadband coherence, linear polarisation, and very short duration, any pulses of radiation which might be detected by these experiments must first pass through the rough lunar surface.…”
Section: Introductionmentioning
confidence: 99%
“…While Askaryan pulses are characterised by their broadband coherence, linear polarisation, and very short duration, any pulses of radiation which might be detected by these experiments must first pass through the rough lunar surface. Current models of the transmission process, as used in simulations to estimate experimental sensitivity [2,6,7,8,9], only deal with the large-scale effects of surface roughness in refracting a pulse. It has also recently been shown that the lunar Askaryan technique will be sensitive to cosmic-ray interactions [10,11], and consequently these particles have become the target of proposed experiments with the SKA [3] -yet previous estimates of lunar surface roughness effects have only modelled neutrino interactions [12,7].…”
Section: Introductionmentioning
confidence: 99%